Dissecting the Immune Stimulation Promoted by CSF-470 Vaccine Plus Adjuvants in Cutaneous Melanoma Patients: Long Term Antitumor Immunity and Short Term Release of Acute Inflammatory Reactants - Pampena, María B.; Cartar, Holliday C.; Cueto, Gerardo Rubén; Levy, Estrella M.; Blanco, Paula A.; Barrio, María M.; Mordoh, José (Frontiers in Immunology, 2018)
As cutaneous melanoma (CM) currently remains with a bleak prognosis, thorough investigation of new treatment options are of utmost relevance. In the phase II/III randomized clinical trial (CASVAC-0401), the repeated immunization of stages IIB-III CM patients with the irradiated, allogeneic cellular CSF-470 vaccine plus the adjuvants bacillus Calmette-Guerin (BCG) and recombinant human granulocyte macrophage colony-stimulating factor (rhGM-CSF) demonstrated a significant benefit over IFN-alpha2B treatment in distant metastasis-free survival. Here we present on the short and long term immune monitoring results after completing the 2 year protocol; a continuation of the previous report by Mordoh et al., 2017. We demonstrate that the repeated CSF-470 vaccinations stimulated a long term cellular and humoral immunity response directed against the vaccine antigens. In the case of two patients, we are able to show that a similar immune response was generated against autologous antigens. Evaluation of inhibitory receptor co-expression on patient´s T cells indicates that the vaccination protocol did not stimulate T cell exhaustion. In order to better understand the basis for the efficacious vaccine responses observed, we investigated the short term immune events following vaccine injection. A significant increase in C-reactive protein (CRP) and IL-6 was observed 24 hours after vaccination, with in vitro studies suggesting IL-6 production occurs in the vaccine site. We demonstrate that CRP enhances the cytotoxicity of peripheral blood mononuclear cells (PBMC) against melanoma cells in an in vitro model. Additionally, CRP stimulates the release of pro and anti-inflammatory cytokines from PBMC. As our results demonstrate that successive vaccinations with CSF-470 plus adjuvants promoted an increase in both anti-tumor innate and adaptive immunity, we propose a subsequent model of action.